(3QjGV NjQĎBHGOi (B((3MjGJ GhQ GOHj NOeGJ(B) ;; Riyåaòz öKöhairåabåadåi haiat awr adbi khadamatu /s - Khan, Khalilullah; (3NGf(B, (3Ndjd Gddgs (Lakhnu : Urdu publisher, 1974)
On the works of Riyåaòz öKöhairåabåadåi, 1853-1935, Urdu poet and Urdu journalist; with special reference to his contribution in Urdu journalism.
Includes bibliographical references
Keywords: Riyåaòz öKöhairåabåadåi; (3QjGV NjQĎBHGOis; Urdu Literature -- India. -- history & Criticism